A comparison of stress perception in international and local first semester medical students using psychometric, psychophysiological, and humoral methods - Huhn, Daniel; Schmid, Carolin; Möltner, Andreas; Herzog, Wolfgang; Nikendei, Christoph (International journal of environmental research and public health, 2018)
(1) Medical doctors and medical students show increased psychological stress levels. International medical students seem to be particularly vulnerable. (2) We compared different methods of assessing stress levels in international and local first year medical students. First, study participants completed questionnaires related to stress, depression, empathy, and self-efficacy (MBI, PSQ, PHQ-9, JSPE-S, and GSE) at three separate points in time (T1 to T3). Second, their heart rate variabilities (HRVs) were recorded in an oral examination, a seminar, and in a relaxing situation. Third, hair samples were collected at the beginning and at the end of the semester to assess the cortisol concentration. (3) Included were 20 international and 20 local first semester medical students. At T1, we found considerable differences between international and local students in the JSPE-S; at T2 in the MBI factor "professional efficacy", the PHQ-9, and in the JSPE-S; and at T3 in the MBI factors "cynicism" and "professional efficacy", the PHQ-9, and in the JSPE-S. International and local students also differed concerning their HRVs during relaxation. Over the course of the semester, international students showed changes in the MBI factors "emotional exhaustion" and "professional efficacy", the PHQ-9, and the GSE. Local students showed changes in the GSE. No effects were found for students' hair cortisol concentrations. (4) All participants showed low levels of stress. However, while international students experienced their stress levels to decrease over the course of the semester, local students found their stress levels to increase.